Combined lung and liver procurement in controlled donation after circulatory death using normothermic abdominal perfusion. Initial experience in two Spanish centers. Issue 1 (29th July 2019) - Miñambres, Eduardo; Ruiz, Patricia; Ballesteros, Maria Angeles; Álvarez, Carlos; Cifrián, Jose Manuel; Atutxa, Lander; Ventoso, Alberto; Castillo, Federico; Gastaca, Mikel
Abstract: Combining simultaneously lung and liver procurement in controlled donation after circulatory death (cDCD) using normothermic abdominal perfusion (NRP) for abdominal grafts and cooling and rapid recovery technique (RR) for the lungs increases the complexity of the procurement procedure and might injure the grafts. A total of 19 cDCDs from two centers using this combined procedure were evaluated, and 16 liver and 21 lung transplantations were performed. As controls, 34 donors after brain death (DBDs) were included (29 liver and 41 lung transplantations were performed). Two cDCD liver recipients developed primary nonfunction (12.5%). No cases of ischemic cholangiopathy were observed among cDCD recipients. The 1‐year and 2‐year liver recipients survival was 87.5% and 87.5% for the cDCD group, and 96% and 84.5% for the DBD group, respectively ( P  = .496). The 1‐year and 2‐year lung recipients survival was 84% and 84% for the cDCD group and 90% and 90% for the DBD group, respectively ( P  = .577). This is the largest experience ever reported in cDCD with the use of NRP combined with RR of the lungs. This combined method offers an outstanding recovery rate and liver and lung recipients survival comparable with those transplanted with DBDs. Further studies are needed to confirm our findings. Abstract : This study demonstrates the feasibility of abdominal normothermic regional perfusion combined with rapid recovery of the lungs and shows an outstanding recovery rate with good function of both liver and lung grafts.